The Effect of Common Currencies on International Trade: A Spatial Econometric Approach - Ali Fegheh Majidi; Khaled Ahmadzadeh; Seyede Fatemeh Najafi Zadeh (فصلنامه پژوهش‌های اقتصادی ایران, 2020)
In recent years, the desire to create a monetary union at the international level has increased. According to economic theory, the formation of monetary unions and the adoption of a common currency encourages economic integration, controls monetary policy instability, reduces transaction costs in trade and can lead to an increase in real income through boosting trade. The proximity and neighborhoods of the countries have been introduced as one of the factors affecting trade and the formation of monetary unions. In this study, given the importance of this issue, the effect of the monetary union on bilateral trade has been investigated using the spatial econometric approach during the period of 2000-2015 for a selected countries of the world. The results of the research show that the effect of common currency on bilateral trade is positive, whose trade will lead to economic growth in the countries. Also, the spatial effects of the shared money and geographical distance have been confirmed. Hence, it can be concluded that countries that are adjacent to each other or have common currency would strengthen the trade between themselves, by creating monetary unions. Also, the results of the spatial econometric approach show that GDP and Trade openness index (in three spatial matrices) and real exchange rate (in the common currency matrix and the modified currency matrix) had a positive and significant effect on bilateral trade between the studied countries.